Recycling old antibiotics with ionic liquids - Prudêncio, C (2020)
Antibiotics are considered one of the great “miracles” of the 20th century. Now in the 21st century in the post-antibiotic era, the miracle is turning into a nightmare, due to the growing problem of the resistance of microorganisms to classic antimicrobials and the non-investment by the pharmaceutical industry in new antimicrobial agents. Unfortunately, the current COVID-19 pandemic has demonstrated the global risks associated with uncontrolled infections and the various forms of impact that such a pandemic may have on the economy and on social habits besides the associated morbidity and mortality. Therefore, there is an urgent need to recycle classic antibiotics, as is the case in the use of ionic liquids (ILs) based on antibiotics. Thus, the aim of the present review is to summarize the data on ILs, mainly those with antimicrobial action and especially against resistant strains. The main conclusions of this article are that ILs are flexible due to their ability to modulate cations and anions as a salt, making it possible to combine the properties of both and multiplying the activity of separate cations and anions. Also, these compounds have low cost methods of production, which makes it highly attractive to explore them, especially as antimicrobial agents and against resistant strains. ILs may further be combined with other therapeutic strategies, such as phage or lysine therapy, enhancing the therapeutic arsenal needed to fight this worldwide problem of antibacterial resistance. Thus, the use of ILs as antibiotics by themselves or together with phage therapy and lysine therapy are promising alternatives against pathogenic microorganisms, and may have the possibility to be used in new ways in order to restrain uncontrolled infections.